2020
DOI: 10.3390/ijerph17041303
|View full text |Cite
|
Sign up to set email alerts
|

A Horticultural Therapy Program Focused on Succulent Cultivation for the Vocational Rehabilitation Training of Individuals with Intellectual Disabilities

Abstract: We aimed to develop a horticultural therapy program for the vocational rehabilitation of individuals with intellectual disabilities and examine its effects. Individuals with intellectual disabilities (n = 28, average age: 33.23 ± 4.9 years) were recruited from a welfare center in Jecheon, South Korea. They participated in eight weekly sessions of a horticultural therapy program consisting of common succulent cultivation techniques at a specialized succulent cultivation farm located in Jecheon, South Korea. Bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Previous literature indicates that horticultural activities can be classified as low-to high-intensity aerobic exercises (Hawkins et al, 2015). Repeated reaching-grasping motions help participants master fine skills, increase grasp and pinch forces, and gain agility (Joy et al, 2020;Lee et al, 2018), which would promote cardiopulmonary endurance and upper-limb flexibility such as muscle activation, movement times, velocity and the angular range of movement of joints (Lee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature indicates that horticultural activities can be classified as low-to high-intensity aerobic exercises (Hawkins et al, 2015). Repeated reaching-grasping motions help participants master fine skills, increase grasp and pinch forces, and gain agility (Joy et al, 2020;Lee et al, 2018), which would promote cardiopulmonary endurance and upper-limb flexibility such as muscle activation, movement times, velocity and the angular range of movement of joints (Lee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that an 18-session horticultural therapy did not significantly improve hand dexterity in patients with disability (e.g., patients with stroke) [ 93 ]. Therefore, most researchers prefer to set a longer course of hand–eye coordination training for individuals with disability, e.g., 20 sessions [ 94 ] or 24 sessions [ 38 ] of training. Assessment of the effectiveness of a horticultural intervention should consider the characteristics of the group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of nature provides a naturalistic milieu to promote speech development using incidental teaching [66], and building functional skills and confidence in real-world settings, including outdoor environments may assist in overcoming disparities in exposure to nature, where those who are more vulnerable likely have less access to nature [35]. Some of these activities could be integrated into prevocational training, with for example, prevocational farm activities [67] and horticulture programs [68], improving health and wellbeing, and a potential role for environmental enhancement (e.g. ecological restoration) activities having been recently highlighted [69].…”
Section: Nature-based Activities Used By Allied Health Professionalsmentioning
confidence: 99%